Generating online map for skudai using the minnesota map server - Abdul Rahman, Alias (2003)

(untitled)
This paper reports a process of familiarizing and generating online map by using free map server, namely, the Minnesota Map Server. This project aims to generate an online map for Skudai area. The process of implementing the Skudai online map forms major discussion of this paper. The paper also highlights the accessibility, advantages and drawbacks of the map server.